PSII-12 The effects of lift crates on sow performance and litter survival - Obermier, Dalton R (J Anim Sci, 2019)
In modern sow farms, pre-weaning mortality (PWM) remains a key barrier to achieving peak productivity and optimizing piglet welfare. Therefore, a total of 270 sows (PIC 1050, 3.6 average parity) were used (May to July 2018) to determine the effect of lift crates in farrowing on sow and piglet performance and litter survival in a commercial setting in southwestern Ontario, Canada. Lift crates are driven by postural changes in the sow which activate a hydraulic lift system (Balance Frame; NOOYEN, Deurne, NL) which temporarily raises a movable sow slat 25 cm above the crate floor. Sows were randomly assigned to 2.44 m × 1.83 m farrowing crates that were 1) conventional or 2) lift crates. Within rooms, litters were standardized to 13 or 14 pigs within 24 h after parturition. Daily sow feed intake was measured using electronic lactation feeders (Gestal SOLO; JYGA Technologies, Inc.). Data were analyzed using the MIXED procedure of SAS (Cary, NC). Sow was the experimental unit. No differences (P > 0.22) were observed for number born alive, stillbirths or mummified fetuses. Sow backfat loss (2.2 vs. 2.5 mm), average daily feed intake (5.67 vs. 5.74 kg) and wean-to-estrus interval (5.27 vs. 5.62 d) were similar (P > 0.16) between conventional and lift crate treatments. However, from birth to cross-fostering, lift crates reduced (P < 0.01) piglet deaths by 55% when compared to conventional crates (0.58 vs. 0.32 piglets). Piglet deaths from cross-fostering to weaning did not differ (P = 0.18, 0.68 vs. 0.54 piglets). Number of pigs weaned (12.62 vs. 12.87) and suckled litter weaning weight (75.7 vs. 75.6 kg) did not differ (P > 0.11) across treatments. These results provide evidence that lift crates can reduce the number of piglet deaths and may improve PWM in sow farms.Keywords: crate, piglet, survival